2017
DOI: 10.1039/c6dt04340b
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of An–X bonding (An = Th, U; X = p-block-based ligands) in pyrrolic macrocycle-supported complexes from the quantum theory of atoms in molecules and bond energy decomposition analysis

Abstract: Good correlations are found between QTAIM BCP and EDA data for a range of Th(iv)- and Th(iii)-p element bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The bond strength of four U–E bonds is the trend of U–Si > U–Sn > U–Ge > U–Pb according to the value of bond order. In addition, the delocalization index (δ) can evaluate the bonding nature, which is a measure of bond order. The values of δ­(U–E) are about 0.5, which can also reveal U–E bonds possess a single-bond feature.…”
Section: Molecular and Electronic Structuresmentioning
confidence: 99%
“…The bond strength of four U–E bonds is the trend of U–Si > U–Sn > U–Ge > U–Pb according to the value of bond order. In addition, the delocalization index (δ) can evaluate the bonding nature, which is a measure of bond order. The values of δ­(U–E) are about 0.5, which can also reveal U–E bonds possess a single-bond feature.…”
Section: Molecular and Electronic Structuresmentioning
confidence: 99%
“…51 Previous theoretical studies have identified that QTAIM analysis can provide insightful information on the bonding nature of actinide complexes. 52,53 The calculated QTAIM parameters of M-N and M-O BCPs in the studied systems are listed in Table 4.…”
Section: Chemical Bonding Analyses Of [An-l] à Complexesmentioning
confidence: 99%
“…The U–Ru bond order of complex 1 is smaller than that of complex 2 , although the U–Ru bond length for the former is shorter than that for the latter. In addition, the values of the delocalization index (DI) for the four U–Ru bonds are 0.557, 0.576, 0.588, and 0.674, respectively, implying single character.…”
Section: Molecular and Electronic Structuresmentioning
confidence: 99%